2022
DOI: 10.1073/pnas.2210490120
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-resident innate-like memory γδ T cells control chronic Staphylococcus aureus infection of mice

Abstract: γδ T cells are involved in the control of Staphylococcus aureus infection, but their importance in protection compared to other T cells is unclear. We used a mouse model of systemic S. aureus infection associated with high bacterial load and persistence in the kidney. Infection caused fulminant accumulation of γδ T cells in the kidney. Renal γδ T cells acquired tissue residency and were maintained in high numbers during chronic infection. At day 7, up to 50% of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…aureus infection can form abscesses and persist in different organs. The kidneys are frequently the most affected ones, displaying high bacterial burdens [ 69 ]. In the present study, the main lesions were identified in the liver and kidneys as foci of neutrophil infiltration with abscess formation.…”
Section: Resultsmentioning
confidence: 99%
“…aureus infection can form abscesses and persist in different organs. The kidneys are frequently the most affected ones, displaying high bacterial burdens [ 69 ]. In the present study, the main lesions were identified in the liver and kidneys as foci of neutrophil infiltration with abscess formation.…”
Section: Resultsmentioning
confidence: 99%
“…Some mice in this study were also found to have a biphasic wave of IL-17 production, with one peak at 3 h and the second at 72 h post-infection, with Vγ4+ γδ T cells at 72 h being primed for later infection and IL-1β independent IL-17 production [18], suggesting a memory function for γδ T cells during acute peritonitis as well. In the kidney, chronic systemic S. aureus infection induced the expansion of a population of kidney-resident γδ T cells that constitutively express CD69 and provide protection against S. aureus [15]. Thus, in mice, S. aureus infection seems to expand both resident and memory γδ T cells.…”
Section: Peritonitismentioning
confidence: 99%
“…Vγ4+ cells increase in number through development [12]. Vγ4+ γδ T cells typically make IFNγ cytokine, while Vγ6+ γδ T cells typically make IL-17 and IL-22 [15]. Thymic signals regulate these cells' subsequent effector function and critical role during early infection stages [16].…”
Section: Introductionmentioning
confidence: 99%
“… 970 , 971 Systemic S. aureus infection led to accumulation of IL-17A + γδ T cells in the kidney for effective infection control. 972 In the infected intestinal tract, Vγ7 + γδ T cells directly kill infected cells by secreting antimicrobial peptides and cytotoxic molecules. 973 In Mtb infected lung tissue, Vγ4 + γδ T cells secrete CXCL2 and TNF to promote neutrophil recruitment and Vγ4 + and Vγ6 + Tγδ17 cells contribute to granuloma formation.…”
Section: γδ T Cellsmentioning
confidence: 99%